Does determinant, capital structure in pharmacy company in indonesia: Finance - Wastam Wahyu Hidayat (Enrichment : Journal of Management, 2023)
This study aims to determine whether there is an influence on asset structure, and sales growth. Liquidity and business risk on the capital structure of pharmaceutical companies listed on the Indonesia Stock Exchange. The sample in this research is a pharmaceutical company consisting of 15 companies from 2018 to 2022. The research method used is multiple linear regression analysis with SPSS-26. The results of the study show that asset structure has no significant effect on capital structure, sales growth has an effect on capital structure, liquidity has an effect on capital structure and Business Risk has no significant effect on the capital structure of pharmaceutical companies listed on the IDX for the 2018-2022 period. Based on table 3.0, it is known that the coefficient of determination or Adjusted R2 is 0.40 or 40%, it can be interpreted that the contribution of the independent variable to the dependent variable is the capital structure of 40% and the remaining 60% by other variables